Effect of Chicken Manure and NPK Fertilizer on the Growth and Yield of Purple Eggplant (Solanum melongena) Mustang F1 Variety - Sari, Nia Kurnia; Budiasih, R; Mulyana, Hudaya (Fruitset Sains : Jurnal Pertanian Agroteknologi, 2022)
The experimental research was carried out in Dawuan Kidul Village, Dawuan District, Subang Regency with an altitude of 700 m above sea level, with a type C climate (somewhat wet) from March 2021 to June 2021. This study aimed to study the effect of the interaction of chicken manure and NPK pearl yaramila fertilizer. Environmental design using a completely randomized design (RAK) factorial pattern, treatment of chicken manure (K) consists of 4 levels, namely k0 = 0 tons ha?¹ (control), k1 = 10 tons ha? k2 = 20 tons ha?¹, k3 = 30 tons ha?¹ and pearl NPK fertilizer Yaramila 16: 16: 16 (Y) consists of 4 levels, namely y0 = 0 kg ha?¹ (control), y1 = 100 kg ha?¹, y2 = 200 kg ha?¹, y3 = 300 kg ha?¹.. The results showed that the effect Chicken manure and pearl yaramila NPK fertilizer had an interaction effect on plant height and number of leaves aged 7 WAP, number of fruits per plant, fruit length, weight per fruit and fruit weight per plant, while the observation of plant height and number of leaves at 3 WAP and 5 MST showed no interaction